Microlearning in the digital age : the design and delivery of learning in snippets - Corbeil, Joseph Rene; Khan, Badrul H. 1958-; Valdés-Corbeil, María Elena (Routledge, 2021)
"Microlearning in the Digital Age explores the design and implementation of bite-sized learning and training in technology-enabled environments. Grounded in research-based best practices and a robust, eight-dimensional framework, this book applies the latest developments in mobile learning, social media, and instructional/multimedia design to one of today's most innovative and accessible content delivery systems. Featuring experts from higher education, information technology, digital gaming, corporate, and other contexts, this comprehensive guide will prepare graduate students, researchers, and professionals of instructional design, e-learning, and distance education to develop engaging, cost-effective microlearning systems"- Resumé vydavatel